Anonymous women : interpretations about women in contemporary turkish paintings 1988-1989. (Istanbul : Urart Sanat Galerisi, 1988)
Günat, Neset ; Erdok, Nese ; Koçak, Nur ; Aksoy, Alaaddin ; Güleryüz, Mehmet ; Uluc, Ömer ; Ata, Mustafa ; Yorozlu, Senol ; Arpacioglu, Hale ; Baykam, Bedri ; Koçan, Hüsamettin ; Öztürk, F. Tülin ; Karamustafa, Gülsün
Anonymous womeninterpretations about women in contemporary turkish paintings 1988-1989, Urart Sanat Galerileri, Istanbul, 1988-1989
boek
Keywords: Turkije